2012
DOI: 10.3390/ijms131216157
|View full text |Cite
|
Sign up to set email alerts
|

The Phorbol Ester Fraction from Jatropha curcas Seed Oil: Potential and Limits for Crop Protection against Insect Pests

Abstract: The physic nut shrub, Jatropha curcas (Euphorbiaceae), has been considered as a “miracle tree”, particularly as a source of alternate fuel. Various extracts of the plant have been reported to have insecticidal/acaricidal or molluscicidal/anthelminthic activities on vectors of medical or veterinary interest or on agricultural or non-agricultural pests. Among those extracts, the phorbol ester fraction from seed oil has been reported as a promising candidate for use as a plant-derived protectant of a variety of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 48 publications
0
21
0
1
Order By: Relevance
“…However, again unlike neem or pyrethrum, its extracts have rarely been used for crop protection. This is so despite several studies undertaken over the past 30 years having demonstrated its effectiveness on some 40 species of pests and a dozen crops (on the field or during storage) and despite a dramatic increase in its cultivation as agrofuel in the tropics and in spite of societal concerns regarding the excessive use of chemical pesticides (Ratnadass and Wink 2012).…”
Section: Biocides Derived From Plants Used As a Substitute For Synthementioning
confidence: 87%
See 1 more Smart Citation
“…However, again unlike neem or pyrethrum, its extracts have rarely been used for crop protection. This is so despite several studies undertaken over the past 30 years having demonstrated its effectiveness on some 40 species of pests and a dozen crops (on the field or during storage) and despite a dramatic increase in its cultivation as agrofuel in the tropics and in spite of societal concerns regarding the excessive use of chemical pesticides (Ratnadass and Wink 2012).…”
Section: Biocides Derived From Plants Used As a Substitute For Synthementioning
confidence: 87%
“…Several examples illustrate this, including the use of essential oils as alternatives to antibiotics in aquaculture in Madagascar (Sarter et al 2011;Randrianarivelo et al 2009Randrianarivelo et al , 2010 or on terrestrial livestock to repel biting insect (e.g., geranium oil used on cattle in Reunion against Stomoxys calcitrans), the use of Jatropha extracts as an anthelmintic (Ratnadass and Wink 2012) or of the extract of cassava leaf (Manihot esculenta) against Haemonchus contortus, a major helminth parasite of small ruminants (Marie-Magdeleine et al 2010). In each case, it was a matter of identifying alternatives to counter the harmful effects of the massive use of anthelmintics on natural soil macrofauna (see 'Hidden soil biodiversity: what potential for agriculture?…”
Section: Use Of the Local Plant Biodiversity In Livestock Rearingmentioning
confidence: 99%
“…This is the case with Jatropha live-hedges planted around market-gardens to keep domestic animals away, or neem wind-breaks planted around orchards, with both also contributing to conservation biological control (Ratnadass and Wink 2012 ).…”
Section: Regarding Botanical Pesticides and Biological Controlmentioning
confidence: 99%
“…The purified PEs could also be converted or transformed chemically into nontoxic compounds with beneficial activities such as the hydrolysis of 12-deoxy-16-hydroxyphorbol that results in the synthesis of 12-deoxyphorbol-13-phenyl acetate, a compound that is considered as a promising adjuvant for antiviral therapy because of its anti-HIV properties (Wender et al, 2008). Some studies had been reported the antifungal and insecticide properties from Jatropha curcas seed cake attributed to the presence of PE , Devappa et al, 2012Ratnadass and Wink, 2012;Saetae and Suntornsuk, 2010).…”
Section: Introductionmentioning
confidence: 99%